2018
DOI: 10.15847/obsobs12420181295
|View full text |Cite
|
Sign up to set email alerts
|

La importancia de la audiencia en diferido frente a la audiencia lineal en la televisión en España

Abstract: Esta investigación intenta cuantificar la importancia de la audiencia en diferido frente a la audiencia lineal o tradicional en el mercado televisivo en España desde una nueva perspectiva basada en la audiencia acumulada de los programas analizados. Planteamos tres hipótesis de investigación: la H1 asegura que el peso de la audiencia en diferido en España continúa siendo muy reducido cuantitativamente frente a la audiencia tradicional; la H2 determina que los géneros con mayor número de telespectadores acumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Thus, we estimate that the extracted results are significant. This research applies the same methodological basis employed by Gallardo-Camacho and Lavín (2018), with the exception that those authors quantified the importance of the timeshifted audience in comparison to the linear audience in the Spanish television market based on the cumulative viewership of the programmes and did not analyse the viewing cycle of the contents as we do in this article. Another study uses a similar method, but it is limited to the analysis of the 10 most watched programmes over just one month and the observation of the timeshifted audience of the thematic and mainstream channels (Gallardo-Camacho & Sierra-Sánchez, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we estimate that the extracted results are significant. This research applies the same methodological basis employed by Gallardo-Camacho and Lavín (2018), with the exception that those authors quantified the importance of the timeshifted audience in comparison to the linear audience in the Spanish television market based on the cumulative viewership of the programmes and did not analyse the viewing cycle of the contents as we do in this article. Another study uses a similar method, but it is limited to the analysis of the 10 most watched programmes over just one month and the observation of the timeshifted audience of the thematic and mainstream channels (Gallardo-Camacho & Sierra-Sánchez, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…With regards to the studies analysing the timeshifted viewing of television programmes, Gallardo-Camacho and Sierra Sánchez (2017, p. 185) analysed the 300 television programmes with the highest timeshifted audience over a month (November 2016) and concluded that "the programmes broadcast in thematic channels have a higher increase in linear audience when taking into account the timeshifted viewing" and that the most viewed thematic channels are those dedicated to fiction. Gallardo-Camacho and Lavín (2018) concluded that fictional contents reach the highest timeshifted audience ratings with 84% and that Spanish TV series stand out with 41% of all accumulated viewership.…”
Section: Studies On the Viewing Cycle Of Television Programmesmentioning
confidence: 99%